Promise and reality of market-based environmental policy in China: Empirical analyses of the ecological restoration program on the Qinghai-Tibetan Plateau. (July 2016) - Wang, Pu; Wolf, Steven A.; Lassoie, James P.; Poe, Gregory L.; Morreale, Stephen J.; Su, Xukun; Dong, Shikui
Highlights: We analyzed the design and implementation of a market-based conservation program in China. The market logic emphasized in policy design was not realized in practice. Implementation failure suggests conservation objectives were not achieved. Survey results show great potential of voluntary market-based program. Scientific measurement, voluntarism, and conditional payments can improve performance of program. Abstract: Environmental conservation programs in China have increasingly emphasized integration of market-based logic into regulatory programs. But the realization of market logic and the effectiveness of such efforts are widely questioned by scientists and policy analysts. We empirically analyze the design, implementation, and outcomes of the ecological restoration program in the Three-Rivers Headwater Region in China, a large-scale conservation scheme aimed at restoring degraded grasslands and improving local livelihoods. Results indicate that the market mechanisms emphasized in the design of the policy were not realized in practice due to inadequate use of scientific measurements, lack of accountability, and poor monitoring and enforcement. Moreover, because enrollment was not voluntary, as is generally expected in market-based programs, there were negative impacts on herders. A household survey (n = 202) of local herders shows that if conservation incentives were properly designed and implemented, 67% would voluntarily participate in the program. Variance recorded in ecological and socioeconomic conditions points to opportunities to use market-based policy instruments to integrate local information into decision making regarding targeting of land conservation and land retirement. The potential of market-based environmental policies can be expanded through commitments to scientific measurement, voluntary participation, and outcome-based payments.